Espécies de Phytophthora associadas à gomose dos citros no estado do Paraná - Caixeta, Marilda Pereira (2010)
The etiology of gummosis comprises a complex of Phytophthora species, with significant effect on citrus culture in Brazil and worldwide. Not much is knew about gummosis in citrus producing areas of the state of Paraná, although it is important disease. Thus, the objective of this work was to identify species of Phytophthora associated with gummosis in citrus producing areas of Paraná. Samples of soil and roots from plants showing symptoms of gummosis were collected from orange and tangerine orchards in the Northern and Ribeira Valley regions of the state. Using fruits of pear cv. D'Anjou as bait, 21 isolates of Phytophthora spp. were obtained in pure culture. In a pathogenicity test using artificial inoculation, all isolates infected seedlings of Citrus limonia Osbeck and induced symptoms of gummosis. All isolates showed mycelial growth at 36°C, with the exception of a single isolate (PR20). All isolates showed mycelial growth at 8°C. All isolates were heterothallic; 20 isolates showed compatibility with the A2 type isolate, resulting in the formation of oospores with amphigynous antheridia, while one isolate (PR20) was compatible with the A1 type isolate, resulting in the formation of oospores with amphigynous antheridia. Analyses of the characteristics of the 21 isolates showed that: 20 isolates formed persistent and papillate sporangia, 25,5 - 58,9 µm long and 18,6 - 49, 6 µm wide. Length-width ratio was 1,3:1, mean papilla depth was 6,1 µm, and mean opening was 5,8 µm; there was abundant production of spherical chlamydospores with diameter varying between 21,7 and 43,4 µm. They showed relatively modest mycelial growth at 8 and 36°C and optimum growth temperature between 24 and 32°C. One isolate (PR20) featured sporangia 40,3 - 65,8 µm long by 27,9 - 37,2 µm wide. That isolate formed persistent sporangia, papillate, bipapillate, and in bizarre shapes. It did not show mycelial growth at 36°C, but did grow at 8°C, with optimum growth temperature between 20 and 28°C. There was no formation of chlamydospore reproductive structure in that isolate. According to these morphophysiological traits, comparing them with those described in the bibliography, 20 isolates were classified as belonging to the species Phytophthora nicotianae and one isolate (PR20) as belonging to P. citrophthora. A molecular analysis of the 21 isolates, examining the sequences from region ITS1-5.8S-ITS2 of rDNA, employing SSCP (Single-Strand Conformation Polymorphism), confirmed the existence of these two species of Phytophthora.